If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 * 4x + 7 + -5x = 8 + (-5)(5x + -6x) + 23 Multiply 4 * 4 16x + 7 + -5x = 8 + (-5)(5x + -6x) + 23 Reorder the terms: 7 + 16x + -5x = 8 + (-5)(5x + -6x) + 23 Combine like terms: 16x + -5x = 11x 7 + 11x = 8 + (-5)(5x + -6x) + 23 Combine like terms: 5x + -6x = -1x 7 + 11x = 8 + -5(-1x) + 23 Remove parenthesis around (-1x) 7 + 11x = 8 + -5 * -1x + 23 Multiply -5 * -1 7 + 11x = 8 + 5x + 23 Reorder the terms: 7 + 11x = 8 + 23 + 5x Combine like terms: 8 + 23 = 31 7 + 11x = 31 + 5x Solving 7 + 11x = 31 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 7 + 11x + -5x = 31 + 5x + -5x Combine like terms: 11x + -5x = 6x 7 + 6x = 31 + 5x + -5x Combine like terms: 5x + -5x = 0 7 + 6x = 31 + 0 7 + 6x = 31 Add '-7' to each side of the equation. 7 + -7 + 6x = 31 + -7 Combine like terms: 7 + -7 = 0 0 + 6x = 31 + -7 6x = 31 + -7 Combine like terms: 31 + -7 = 24 6x = 24 Divide each side by '6'. x = 4 Simplifying x = 4
| 3x+3(-2x)=x-3 | | 3(m+5)= | | 7(2x-1)=4x+3 | | g(x)=-3x^2+30x-77 | | 114=19y | | p^2(p^2-4)=3p^2+-8 | | 3*4x=35+5x | | 9w=5670 | | p^2(p^2-4)=3p^2-8 | | -16x^2+105x-34= | | 2*4x+4=28 | | -16x^2-105x-34= | | (5x-15)(2-x)=0 | | 10-4x=x-16-3x | | 9x+3=5x+3 | | 12=3-5k | | 9x-6x+3=7x-2x | | 2(3-x)=3(x+15) | | 21=5+33t-16t^2 | | 5x-9=2x+14 | | 800=.4x | | x^2+5y^2-4xy+6y+10=1 | | x^3-x^2-4x+24=0 | | 5x-3(4x-1)=7-2(7x+2) | | (-3x+1+3)(-3x+1-3)=0 | | 4(3x+5)-5(4x-3)=3 | | p=16w+w+12 | | p=16w | | 4x^2-50x+40=0 | | w=-12+L | | w+12=L | | 2x+3y-14=0 |